Regulation of follicular activation signaling pathways by in vitro inhibition of YAP/TAZ activity in mouse ovaries - Melody Devos; Joana Dias Nunes; Nathalie Donfack Jiatsa; Isabelle Demeestere (Scientific Reports, 2023)
Abstract The Hippo pathway plays a crucial role in the regulation of follicular activation, which constitutes the first step of the folliculogenesis process. Disruption of this pathway occurs in several non-physiological contexts, after fragmentation for ovarian tissue cryopreservation procedures or chemotherapy exposure, leading to massive follicular growth and depletion. This study aimed to investigate the effect of controlling the Hippo pathway using verteporfin (VERT) during in vitro ovarian culture and to evaluate its potential preventive effects on chemotherapy-induced follicle activation using a mouse model. After exposure of cut ovaries to different concentrations of VERT for 3 h, a dose-dependent effect of VERT was observed that reached significant inhibition of YAP activity at 3 µmol/L. To assess the potential effect of controlling chemotherapy-induced Hippo pathway disruption, whole mouse ovaries were exposed to VERT alone or as a co-treatment with 4-hydroperoxycylophosphamide (4HC). VERT co-treatment prevented chemotherapy-induced YAP activation but had a limited impact on downstream effector gene, Ccn2. Surprisingly, VERT co-treatment also prevented mTOR and survival signaling pathway alterations following chemotherapy exposure. These results suggest an interaction between the two main signaling pathways regulating follicle activation and a protective effect of VERT on 4HC-induced DNA damage.